2016
DOI: 10.19084/rca15083
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de sementes de arroz com silício e qualidade fisiológica das sementes

Abstract: A utilização de silício é uma tecnologia limpa do ponto de vista ambiental, que pode conferir vários benefícios para as plantas. O objetivo do trabalho foi avaliar o efeito da aplicação de diferentes doses e fontes de silício, via tratamento de sementes, na qualidade fisiológica das sementes tratadas e produzidas, a partir de plantas oriundas das sementes recobertas com silício. O delineamento experimental utilizado foi em blocos casualizados, em esquema fatorial 3x5 (fontes de silício: Caulim, Escória de Forn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
3
4
0
2
Order By: Relevance
“…The same dose of rice hulls used by those authors promoted a 33% increase in the RL of rice cv. BRS Querência [34]. These findings corroborate ours, in which the coating with CS + PVA promoted an 18% increase in RL, which confirms this effectiveness of calcium silicate in RL.…”
Section: Resultssupporting
confidence: 88%
“…The same dose of rice hulls used by those authors promoted a 33% increase in the RL of rice cv. BRS Querência [34]. These findings corroborate ours, in which the coating with CS + PVA promoted an 18% increase in RL, which confirms this effectiveness of calcium silicate in RL.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were found in coated seeds of barley, wheat and rice (Tavares et al, 2012(Tavares et al, , 2014Corlett et al, 2014;Tunes et al, 2014). However, Oliveira et al (2016) verified that improved Si doses propitiate increase in the number of normal seedlings for FGC in rice.…”
Section: Resultssupporting
confidence: 78%
“…The distribution uniformity, due to small amounts of nutrients applied during the seeds coating process, makes the element stay in direct contact with the emission of the first roots, meeting the demands during the crop initial development and indirectly aggregating value to the seeds (Tunes et al, 2012). The silicon (Si) is a mineral element that bestow several benefits to the plants and has shown positive results during the initial development of barley (Corlett et al, 2014), rice (Tunes et al, 2014;Oliveira et al 2016) and soybean (Rufino et al, 2017). Considered potentially benefic or utile to crops, it assists in the plants defense against biotic stresses (disease and pests) and abiotic (stresses by water and salt, toxicity to heavy metals, high radiation, high or low temperature and nutrient imbalance) (Barbosa et al, 2015;Debona, Rodrigues, & Datnoff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results found in Table 4, it was observed that the SDI in Ultra stood out among the others with an average of 0.21 cm in the ST CRU, which in turn was the ST that provided the highest averages among the STs in the studied cultivars. Silva et al (2018) and Oliveira et al (2015) found no statistical difference for the SDI, attributing this result to good quality seeds, a factor that standardizes this variable.…”
Section: Resultsmentioning
confidence: 88%